Urban developments in northeastern Mesopotamia from the ninevite V to the neo-assyrian periods: excavations at Bassetki - Pfälzner, Peter; Qasim, Hasan A.; Puljiz, Ivana; Sconzo, Paola; Faist, Betina (Zeitschrift für Orient-Archäologie, 2018)
The excavations at Bassetki aim at diachronically investigating a Northern Mesopotamian city. Layers of the Ninevite V period, the Early Middle-Tigris III period, the Old- Babylonian time, the Mittani period, the Middle- and Neo-Assyrian and the Islamic time have been exposed. The discovery of a cuneiform archive made it possible to identify the site with the city of Mardama, a provincial capital of the Middle Assyrian Empire.